Robust high-dimensional alpha test for conditional time-varying factor models. Issue 2 (4th March 2023) - Zhao, Ping
Abstract : This paper considers the problem of testing the presence of alpha in high-dimensional conditional time-varying factor model. We proposed a spatial-sign-based test procedure which is robust and efficient for heavy-tailed distributions. We established the theoretical properties of the proposed test statistic under some mild conditions. Simulation studies and a real data example also show the superior of our test procedure to the existing methods.